2003
DOI: 10.1016/s0032-9592(02)00318-7
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater denitrification process—the influence of methanol and kinetic analysis

Abstract: The aim of this work was to achieve rapid nitrate removal from synthetic wastewater (SW) without nitrite accumulation and to improve the economic effectiveness of the process. For that purpose, experiments were carried out to determine the influence of methanol on denitrification rate in batch assays and in the continuous-flow stirred cultures. Nitrate Á/N (200 mgNO 3 ( Á/N/l) was reduced under anoxic conditions during approximately 4 Á/6 h for the MeOH/NO 3 ( Á/N ratio above 2.5. Nitrite concentration was ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…4 and 5). Gas production was also measured, as described in our previous papers (Foglar and Briški 2003;Foglar et al 2005). At the nitrate loading rate of 11.76 mg NO 3 --N L -1 the generated nitrogen gas volume accounted for 9.7 mL N 2 L -1 h -1 which was in agreement with the previously published data (Clifford and Liu 1993).…”
Section: Nitrate Removal With Bacterial Cells Attached To Zeolitesupporting
confidence: 88%
See 2 more Smart Citations
“…4 and 5). Gas production was also measured, as described in our previous papers (Foglar and Briški 2003;Foglar et al 2005). At the nitrate loading rate of 11.76 mg NO 3 --N L -1 the generated nitrogen gas volume accounted for 9.7 mL N 2 L -1 h -1 which was in agreement with the previously published data (Clifford and Liu 1993).…”
Section: Nitrate Removal With Bacterial Cells Attached To Zeolitesupporting
confidence: 88%
“…and Paracoccus sp. were the only true denitrifiers (Zellner et al 1995;Glass and Silverstein 1998;Foglar and Briški 2003). Paracoccus and Pseudomonas bacterial genera being such, their presence in mixed culture obviously accomplished complete nitrate removal with minimum nitrite accumulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Denitrification rate had a negligible change, and was maintained in the range of 9-10 mg/(L h) with 20-50 mg/L of initial concentration of NO 3 -N, indicating a zero-order kinetic model can be used to described the denitrification process under this condition (Foglar and Briski 2003). Several studies have shown that denitrification rate increased consistently with an increase in the initial NO 3 -N concentration using soluble carbon sources (Elefsiniotis and Li 2006), which conflicts with obtained results.…”
Section: Resultsmentioning
confidence: 93%
“…N 2 ) during respiratory denitrification (Lee and Welander, 1996). The denitrification process depends on a number of factors, including change in environmental conditions (temperature and pH), dissolved oxygen and the presence or accumulation of nitrite during the process (Foglar and Briški, 2003). Critically important amongst these factors is the presence and nature of the electron donor, which is usually an organic carbon source (Lee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%